Megatibicen n. gen., a new North American cicada genus (Hemiptera: Cicadidae: Cicadinae: Cryptotympanini) - Sanborn, Allen F.; Heath, Maxine S. (Zootaxa, 2016)
The genus Tibicen has had a confusing history (see summary in Boulard and Puissant 2014; Marshall and Hill 2014; Sanborn 2014). Boulard and his colleague (Boulard 1984; 1988; 1997; 2001; 2003; Boulard and Puissant 2013; 2014; 2015) have argued for the suppression of Tibicen and the taxa derivatived from it in favor of Lyristes Horváth. Boulard’s argument for suppression was first described in Melville and Sims (1984) who presented the case for suppression to the International Commission on Zoological Nomenclature with further comments made by Hamilton (1985), Boulard (1985), and Lauterer (1985). A lack of action resulted in additional comments being published in 2014 again supporting the retention (Sanborn 2014; Marshall and Hill 2014) or the suppression (Boulard and Puissant 2014) of Tibicen.